Edward Daniels Delusion in the Martin Scorsese’s Movie “Shutter Island” - Muh. Fauzi Razak; Nur Sapta Riskiawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the movie “Shutter Island” by Martin Scorsese there is a character Edward Daniels that experience delusion. The aims of this research are to describe the types of delusional disorder on the major character in the Scorsese’s movie “Shutter Island” and the treatments are used to cure major character’s delusion in the movie. The writer used descriptive qualitative method and psychological approach. The writer found that the movie “Shutter Island” by Martin Scorsese showed the types of delusional disorder experienced by major characters, they are grandiose types, jealous types, persecutory types, and somatic types. The disorder needs to be treated before it becomes chronic. Hopefully, this research can contribute to education as an analysis of literary work.